The regulation of transcription elongation in embryonic stem cells - Wang, Xuepeng; Fan, Yudan; Wu, Qiang (Frontiers in Cell and Developmental Biology, 2023)
Transcription elongation is a fundamental molecular process which is accurately regulated to ensure proper gene expression in cellular activities whereas its malfunction is associated with impaired cellular functions. Embryonic stem cells (ESCs) have significant value in regenerative medicine due to their self-renewal ability and their potential to differentiate to almost all types of cells. Therefore, dissection of the exact regulatory mechanism of transcription elongation in ESCs is crucial for both basic research and their clinical applications. In this review, we discuss the current understanding on the regulatory mechanisms of transcription elongation mediated by transcription factors and epigenetic modifications in ESCs.